Cyanobacterial Heterocysts - Kumar, Krithika (Cold Spring Harbor Laboratory Press, 2010)
Many multicellular cyanobacteria produce specialized nitrogen-fixing heterocysts. During diazotrophic growth of the model organism Anabaena (Nostoc) sp. strain PCC 7120, a regulated developmental pattern of single heterocysts separated by about 10 to 20 photosynthetic vegetative cells is maintained along filaments. Heterocyst structure and metabolic activity function together to accommodate the oxygen-sensitive process of nitrogen fixation. This article focuses on recent research on heterocyst development, including morphogenesis, transport of molecules between cells in a filament, differential gene expression, and pattern formation.